2015
DOI: 10.1021/am509231k
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Oil from Oil Sands Using Thermoresponsive Polymeric Surfactants

Abstract: Several thermoresponsive block copolymers constituted of a poly(ethylene glycol) (PEG) and a poly(2-(2-methoxyethoxy) ethyl methacrylate) (PMEO2MA) block were prepared by Atom Transfer Radical Polymerization (ATRP) and their ability to extract oil from oil sands was evaluated. The chemical composition of the PEG113-b-PMEO2MAX block copolymers was determined by 1 H NMR and Gel Permeation Chromatography (GPC) with X-values ranging between 48 and 80. Aqueous solutions of block copolymers showed a cloud point of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The micelles preloaded with the model drug Nile Red will form hydrogels upon heating to physiologic temperature (37 °C), and the resulting hydrogels demonstrated reactive oxygen species (ROS)- dependent drug release [ 26 ]. Duhamel et al demonstrated that poly(ethylene glycol)- b -poly(2-(2-methoxyethoxy) ethyl methacrylate) (PEG- b -PMEO 2 MA) has the ability to extract oil from oil sands [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The micelles preloaded with the model drug Nile Red will form hydrogels upon heating to physiologic temperature (37 °C), and the resulting hydrogels demonstrated reactive oxygen species (ROS)- dependent drug release [ 26 ]. Duhamel et al demonstrated that poly(ethylene glycol)- b -poly(2-(2-methoxyethoxy) ethyl methacrylate) (PEG- b -PMEO 2 MA) has the ability to extract oil from oil sands [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heavy oil refers to the crude with a low API gravity (<20° API) and high viscosity (>100 cP) at reservoir conditions. As a massive resource, heavy oil accounts for more than 70% of total original oil in place (OOIP), which is especially abundant in Canada (mainly Alberta), Venezuela (the Orinoco Belt), and China (Liaohe, Xinjiang, Shengli, Henan oilfields, and Bohai Offshore). With the gradual depletion of conventional light and medium oil, more attention is paid to how to effectively and economically recover heavy oil. …”
Section: Introductionmentioning
confidence: 99%
“…5−7 Examples include cationic surfactants, which have low adsorption on calcite and are appropriate for use in carbonate reservoirs, 8 sulfonated polymers grafted on nanoparticles, which adsorb weakly on silica, 9 zwitterionic polymers with tunable adsorption on carbonate surfaces, 10 and many others. 1,11 One of the major challenges in practical EOR applications of polymers is their poor retention due to the adsorption of polymers inside pores or on rock surfaces of reservoirs and their loss due to fluid flow. 9,10 Polymer flooding at high temperatures and pressures, typical of oil reservoir conditions, can lead to other challenges, such as precipitation and degradation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The method’s efficacy depends on the nature of polymers used and their interactions with the oil and the surfaces of the porous mineral rocks of the oil reservoirs. Walls of conventional oil reservoirs are frequently composed of kaolinite in sandstone reservoirs, calcite and dolomite in carbonate reservoirs, while unconventional rock reservoirs, like shale, can be composed of kaolinite, illite, calcite, dolomite, and other minerals. Selection of polymers for EOR processes is dependent on the type of rocks and materials that predominate within reservoirs. Examples include cationic surfactants, which have low adsorption on calcite and are appropriate for use in carbonate reservoirs, sulfonated polymers grafted on nanoparticles, which adsorb weakly on silica, zwitterionic polymers with tunable adsorption on carbonate surfaces, and many others. , …”
Section: Introductionmentioning
confidence: 99%